AHMADIYAH DI LOMBOK RESPON PEMERINTAH DAERAH TERHADAP PEMENUHAN HAK-HAK SIPIL JEMAAT AHMADIYAH DI MATARAM PASCA SKB 2008 - Ismail, Zaky (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2014)
This article is a study about the local government’s responses to the fulfillment of civil rights of the Ahmadiyah followers in Lombok, Mataram. The research questions are: first, how is the attitude of the Ahmadiyah followers to obtain their political and social rights as citizens in shelters; second, how are the local government’s of the West Nusa Tenggara Province responses to the civil rights of the Ahmadiyah groupin the refugee camps. Using qualitative approach, the results of the study indicatethat the Ahmadiyah members feel themselves asthe disadvantaged citizens in terms of the enjoyment of civil rights. They consider themselves the victims of such violation ofrights as the right to be recognized as citizens, the right as refugees, the right to property, the right to security, and the right of equality before the law. In the case of the local government, however, the Ahmadiyah groupsees that the government has provided them the full rights of citizenship.